Experimental and numerical analysis on the mooring tensions of the coupled tunnel-barge system in waves. (1st September 2021) - Yang, Can; You, Zaijin; Bai, Xiaodong; Liu, Zhongbo; Geng, Jing; Johanning, Lars
Abstract: This paper presents the experimental results for a 1:50 scaled model of an immersed tunnel element suspended from a twin-barge in tank tests. A compliant four leg catenary mooring system using steel link chains in the physical tests is investigated. The corresponding numerical model is developed to simulate the mooring characteristics and the fully coupled dynamic responses of the tunnel-barge system, using the hydrodynamic properties from the diffraction/radiation potential code. To validate the numerical model, preliminary static, quasi static, decaying test and regular wave test were carried out for the comparison. The main findings demonstrate that the mooring tensions of the tunnel-barge system are comparatively lower than that of the tunnel suspended from a fixed platform, particularly when subjected to long period irregular waves. The maximum mooring load of the tunnel element is significantly affected by the natural frequencies of both the tunnel and twin-barge. For the method of the tunnel element immersion presented in this paper, large local peaks in mooring tensions occur at excitation periods of waves close to the tunnel-barge resonance of roll, which should be avoided during design for an appropriate mooring system. Highlights: A moored tunnel element suspended from a twin-barge model is numerically investigated to study the effect of different wave conditions and immersion depths on the mooring characteristics of the tunnel element. To validate the numerical model, preliminary static, quasi static, decaying test and regular wave test were carried out for the comparison. The mooring tensions of the tunnel-barge system are comparatively lower than that of the tunnel suspended from a fixed platform, particularly when subjected to long period irregular waves. The influence of the dynamic response of the floating twin-barge on the tunnel mooring loads introduces an important aspect in the coupled behavior that needs to be considered in the early design phase. The mooring tensions of the tunnel element in the coupled system increased with the wave period until reached a local peak and then occurs a decreasing trend.